2018
DOI: 10.18632/aging.101537
|View full text |Cite
|
Sign up to set email alerts
|

p62 /SQSTM1 coding plasmid prevents age related macular degeneration in a rat model

Abstract: P62/SQSTM1, a multi-domain protein that regulates inflammation, apoptosis, and autophagy, has been linked to age-related pathologies. For example, previously we demonstrated that administration of p62/SQSTM1-encoding plasmid reduced chronic inflammation and alleviated osteoporosis and metabolic syndrome in animal models. Herein, we built upon these findings to investigate effect of the p62-encoding plasmid on an age-related macular degeneration (AMD), a progressive neurodegenerative ocular disease, using spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…This protein is widely recognized for its multiple roles in the cell and also emerged as a key factor in AD [ 30 ]. In addition, previous data demonstrated that the administration of a p62-encoding plasmid exerted a powerful anti-osteoporotic, anti-inflammatory, and retinoprotective activity in animal models [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is widely recognized for its multiple roles in the cell and also emerged as a key factor in AD [ 30 ]. In addition, previous data demonstrated that the administration of a p62-encoding plasmid exerted a powerful anti-osteoporotic, anti-inflammatory, and retinoprotective activity in animal models [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Already by the age of ~3–4 months, 100% of OXYS rats develop clinical signs of retinopathy against the background of a reduction in the transverse area of the retinal pigment epithelium (RPE), impairment of choroidal microcirculation, and retinal thinning [ 8 ]. The progression of these abnormalities in OXYS rats with age is accompanied by a significant reduction in the thickness of the photoreceptor cell layer and a decrease in the number of photoreceptor cell nuclei in the outer nuclear layer (ONL), especially in the central part of the retina [ 9 , 10 ]. The significant pathological changes in the RPE manifest themselves as excessive accumulation of lipofuscin and amyloid in the RPE regions and disturbances in the morphology of the RPE sheet, including an increase in the proportion of multinucleated cells, hypertrophy, distortion of cell shape, and reactive gliosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that a suitable experimental model of AMD is senescence-accelerated OXYS rats, which spontaneously develop a phenotype similar to human age-related disorders including AMD-like retinopathy [5][6][7][8][9][10][11]. Retinopathy that develops in OXYS rats already at a young age corresponds (in terms of clinical manifestations and morphological characteristics) to the dry atrophic form of AMD in humans.…”
Section: Introductionmentioning
confidence: 99%